History, status and future of Australia's native Sydney rock oyster industry. Issue 3 (15th January 2015) - Schrobback, Peggy; Pascoe, Sean; Coglan, Louisa
Abstract : The Sydney rock oyster ( Saccostrea glomerata ) (SRO) is an oyster species that only occurs in estuaries along Australia's east coast. The SRO industry evolved from commercial gathering of oyster in the 1790s to a high production volume aquaculture industry in the 1970s. However, since the late 1970s the SRO industry has experienced a significant and continuous decline in production quantities and the industry's future commercial viably appears to be uncertain. The aim of this study was to review the history and the status of the SRO industry and to discuss the potential future prospects of this industry. This study summarised findings of the existing literature about the industry and defined development stages of the industry. Particular focus was put on the more recent development within the industry (1980s-present) which has not been covered adequately in the existing literature. The finding from this study revealed that major issues of the industry are linked to the management of prevailing diseases, the handling of water quality impairments from increasing coastal development, increasing competition from Australia's Pacific oyster ( Crassostrea gigas ) industry and the current socio-economic profile of the industry. The study also found that policy makers are currently confronted by the dilemma of saving a "dying art". Findings from this industry review may be vital for current and future fisheries managers and stakeholders as a basis for reviewing industry management and development strategies. This review may also be of interest for other aquaculture industries and fisheries who are dealing with similar challenges as the SRO industry.